34‐1: Evaluating and Minimizing Color Distortion in Wide‐Gamut Displays Due to Variations of Cone Fundamentals among Color‐Normal Observers. Issue 1 (28th June 2021) - Whitehead, Lorne; Smet, Kevin A.G.; Webster, Michael
Abstract : Narrowband three‐primary displays cause observer‐based metameric failure, whereby normal variations in color vision cause individuals to perceive display colors differently. This problem is reduced with broadband primaries, but so is color gamut. Another solution is to use six narrowband primaries, but this is considered impractical. Color error arises from the diversity of cone fundamentals among color‐normal observers. We recently developed a better way to assess this problem and reduce it. This enables both color accuracy and increased gamut, by optimizing the wavelengths in a four narrowband primary system that is compatible with current hardware and video signals.